Diagnostic value of exosome-derived lncRNA PITPNA-AS1 in lung cancer - Chen, Mujin; Feng, XiaoHui; Liu, ChengChen; Huang, Yan; Su, LiJuan; Li, XiaoFeng; Zhu, JinFeng (Frontiers in Immunology, 2025)
BackgroundLung cancer is one of the most lethal types of cancer, and effective diagnostic biomarkers are required. There is increasing evidences that exosome-secreted lncRNAs could play an important role in lung cancer diagnosis. However, the diagnostic value and molecular mechanism of the key lncRNA PITPNA-AS1 in lung cancer remain unclear.MethodsqRT-PCR was conducted to determine the levels of exosomal lncRNA PITPNA-AS1 in pleural effusions from lung adenocarcinoma, squamous cell lung carcinoma, and small cell lung cancer patients. Receiver operating characteristic (ROC) curve analyses were used to evaluate the diagnostic accuracy of PITPNA-AS1. Its role in lung cancer development was determined by a series of experiments, including CCK-8, flow cytometry, and transwell assays. RNA pull-down and RNA immunoprecipitation assays were carried out to examine the interaction between PITPNA-AS1 and Fragile X messenger ribonucleoprotein 1 (FMR1).ResultsWe discovered PITPNA-AS1 in exosomes from lung cancer patients. Its expression was significantly increased in lung cancer patients compared to non-cancer patients, and it was strongly associated with tumor stage, lymph node metastasis, and distant metastasis in all lung cancer subtypes assessed (all p<0.05). ROC curve analyses demonstrated that exosomal PITPNA-AS1 had a high accuracy for differentiating among lung cancer subtypes. Furthermore, PITPNA-AS1 boosted H1299 and A549 cell proliferation, migration, and invasion. Mechanistically, via direct interaction, PITPNA-AS1 increased FMR1 stability by preventing its ubiquitination.ConclusionsThese results reveal that exosome-derived lncRNA PITPNA-AS1 acts as an oncogene to promote malignant biological behaviors and is a promising diagnostic biomarker in lung cancer.